The Effect of Upper Removable Orthodontic Appliances on Oral Candidal Mucosal Carriage - Alan Issa Saleem (College of Dentistry/ University of Baghdad, 2016)
Background: Treatment of malocclusions using removable orthodontic appliances may prepare new stagnant areas susceptible for colonization and retention of Candida species, therefore; the aim of this study was to investigate the effect of upper removable orthodontic appliances on the mucosal Candidal count in group of apparently healthy orthodontic patients. Materials and Methods: Patients enrolled in this study were children aged 8-12 years having upper removable orthodontic appliances. Candidal counts at six mucosal sites were estimated using Imprint Culture method before, 14 and 28 days during orthodontic therapy. Results: Whole mouth and individual mucosal sites for Candidal counts increase significantly during treatment with upper removable orthodontic appliances. Conclusion: The results suggest that removable orthodontic appliances treatment promotes an increase in Candida counts. Furthermore, removable appliance therapy had a positive transient influence upon the prevalence and density of oral candidal carriage. This can indicate a more cautious approach when providing orthodontic treatments for immunocompromised children regarding the increased possibility of candidal infection